Pneumonia em pacientes sob ventilação mecânica por Staphylococcus aureus resistentes à Meticilina, internados em UTI de adultos : aspectos microbiológicos, clínicos e epidemiológicos - Cardoso, Renata Lima (2007)
Objectives: Investigate the participation of the S. aureus, as etiological agent of the pneumonias associated to the mechanical ventilation (PAVs) and evaluate the colonization as risk factor of PAV and the prognostic of the treatment when correct or incorrect. Material and Methods: The study was prospective, longitudinal, performed from March/2005 to February/2006, including 500 patients admitted in the UTI - adult, with 15 beds of the Hospital of Clinics of the Federal University of Uberlândia. All the patients were submitted to the colonization research by S. aureus in different sites. The PAVs were defined based on clinical, radiological criteria and microbiological count 106 UFC/ml in the tracheal aspirate. Results: The S. aureus was the most frequent agent in the PAVs. The participation of samples of MRSA was inferior (42,1%) to the one observed by MSSA (57,9%). In the patients with PAV by S. aureus, a most frequent colonization was observed by MRSA. The samples of MRSA behaved as multi resistant and the ones resistant to clindamycin, showed, in the majority, as from the constituent phenotype (60%). In PAVs by S. aureus, the mortality rate was high in the subgroup MRSA (37,5%). Conclusion: The more and more frequent presence of S. aureus in PAVs has been becoming a serious problem, raising the necessity of a reflection about the need of the introduction the de-escalonation of antibiotics regimens.